Macrophage-derived IL-1α promotes sterile inflammation in a mouse model of acetaminophen hepatotoxicity. Issue 11 (November 2018) - Zhang, Chao; Feng, Jin; Du, Jun; Zhuo, Zhiyong; Yang, Shuo; Zhang, Weihong; Wang, Weihong; Zhang, Shengyuan; Iwakura, Yoichiro; Meng, Guangxun; Fu, Yang-Xin; Hou, Baidong; et al.
Abstract The metabolic intermediate of acetaminophen (APAP) can cause severe hepatocyte necrosis, which triggers aberrant immune activation of liver non-parenchymal cells (NPC). Overzealous hepatic inflammation determines the morbidity and mortality of APAP-induced liver injury (AILI). Interleukin-1 receptor (IL-1R) signaling has been shown to play a critical role in various inflammatory conditions, but its precise role and underlying mechanism in AILI remain debatable. Herein, we show that NLRP3 inflammasome activation of IL-1β is dispensable to AILI, whereas IL-1α, the other ligand of IL-1R1, accounts for hepatic injury by a lethal dose of APAP. Furthermore, Kupffer cells function as a major source of activated IL-1α in the liver, which is activated by damaged hepatocytes through TLR4/MyD88 signaling. Finally, IL-1α is able to chemoattract and activate CD11b+ Gr-1+ myeloid cells, mostly neutrophils and inflammatory monocytes, to amplify deteriorated inflammation in the lesion. Therefore, this work identifies that MyD88-dependent activation of IL-1α in Kupffer cells plays a central role in the immunopathogenesis of AILI and implicates that IL-1α is a promising therapeutic target for AILI treatment.